A reinvenção da acupuntura: estudo sobre a transplantação da acupuntura para contextos ocidentais e adoção na sociedade brasileira - Moraes, Maria Regina Cariello (2007)
The chinese medicine originally was the part of magic-religious universe, fundamented on the taoist cosmology and later suffered due to the influence of confucionism and budism. It passed through several modifications during the history of milleniums of China; was secularized after the Cultural Revolution and assimilated western characteristics in the recent times. The application of needles is one of its teraphic tecniques, which has been translated as acupuncture to the western culture since XVII century. The ample diffusion of acupuncture in the last decades which was accompanied by the socio-historical transformations permitted its assimilation to the new cultural contexts. The eastern medicinal techniques were valued in the west during the period of counter culture, which contested the rational cientific knowledge as unique producer of the truth e cartesian separation between body, mind and spirit. Parallelly the imporation of medicinal treatments, paved the way in the modification in the western religious conceptions and emerged new corporities which favoured the adoption of eastern practices of health. With the result of the process of inclusion of acunpuncture in the western contexts, new ways of practicing the chinese therapy have emerged, several reinventions of the art of application of needles have taken place in order to adapt to the western cosmovision and to the life in modern times. The objective of this dissertation is to present the historical reconstruction of transformation of medicine in China and in the West; the transplantation of acupuncture as an element desconnected to the original simbolic universe to the western countries, and the process of adoption of acupuncture in the brazilian society, delienating the possible modes of practing acupuncture in contemporary Brasil